2022
DOI: 10.1200/go.22.00032
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Treatment and Outcomes in Epithelial Ovarian Cancer: A Retrospective North Indian Single-Institution Experience

Abstract: PURPOSE Ovarian cancer (OC) is ranked as the third most common gynecologic cancer in various Indian cancer registries. In India, OC is seen in the younger age group, with a median age < 55 years being reported by most of the studies. The majority of patients are diagnosed in advanced stage (70%-80%), where the long-term (10-year) survival rate is poor, estimated at 15%-30%. The aim of this study was to evaluate clinical epidemiology, treatment patterns, and survival outcomes in patients with epithelial OC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…In comparison, all other stage groups had similar survival rates (20–26 months). These data differ from the results of the article published by Rajendra Kumar Meena in 2022 in JCO Global Oncology, according to which stage I and II patients have better survival than more advanced-stage groups do [ 31 ]. An Italian study that was carried out by Gadducci et al also showed statistical significance between survival after recurrence and initial clinical stage (I, IIA vs. IIB–IV) [ 35 ].…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In comparison, all other stage groups had similar survival rates (20–26 months). These data differ from the results of the article published by Rajendra Kumar Meena in 2022 in JCO Global Oncology, according to which stage I and II patients have better survival than more advanced-stage groups do [ 31 ]. An Italian study that was carried out by Gadducci et al also showed statistical significance between survival after recurrence and initial clinical stage (I, IIA vs. IIB–IV) [ 35 ].…”
Section: Discussioncontrasting
confidence: 94%
“…This was probably because the median age of patients in Armenia was 55, which is considerably younger compared to statistics from the United States, where the median age for this disease is 63 [ 29 ], and also lower than that reported in Japanese studies, where the median age of patients at relapse was reported as 59 [ 30 ]. Conversely, in India, ovarian cancer is present in a younger age group, with a median age < 55 years reported by most studies, and even <50 years in some regions of the country [ 31 ]. This phenomenon might be attributed to underdiagnosis and undertreatment of ovarian cancer among the elderly population in limited-source settings.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports a significant difference in the mean value of CA125 tumor marker between the cases and controls. Comparable results were reported by other studies 23–25 …”
Section: Discussionsupporting
confidence: 89%
“…Comparable results were reported by other studies. [23][24][25] Majority of cases belonged to stage III and stage IV of the disease at the time of diagnosis. Similar findings have been reported in other Indian studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation